Experimental study on seismic performance of a low-energy consumption composite wall structure of a pre-fabricated lightweight steel frame. Issue 4 (10th April 2019) - Suizi, Jia; Wanlin, Cao; Zibin, Liu
Abstract : This study developed a low-energy consumption composite wall structure constructed with a pre-fabricated lightweight steel frame that is suitable for houses in villages and towns and evaluated its anti-seismic performance. A low-reversed cyclic-loading test was conducted on four full-scale pre-fabricated structure specimens, including a lightweight, concrete-filled steel tube (CFST) column frame specimen (abbreviated as SFCF), a lightweight CFST column frame composite wall specimen (abbreviated as SFCFW), an H-steel column frame specimen (abbreviated as HSCF) and an H-steel column frame composite wall specimen (abbreviated as HSCFW). The failure characteristics, hysteretic behaviour, strength, rigidity, ductility and energy dissipation capacity of each specimen were compared and analysed. The results demonstrated that the pre-fabricated, double L-shaped beam–column joint with a stiffener rib which was proposed in this study worked reliably and exhibited good anti-seismic performance. The yield, ultimate and frame yield loads of the specimen SFCFW were 1.72, 1.80 and 2.03 times higher than those of specimen SFCF. The yield load, ultimate load and frame yield loads of specimen HSCFW were 1.27, 1.68 and 1.82 times higher than those of specimen HSCF. This indicates that the embedded composite wall contributed significantly to the horizontal bearing capacities of the SFCF and HSCF specimens. The embedded composite wall was divided into multiple strip-shaped composite panels during failure and achieved a stable support for the frame in the later stages of elastoplastic deformation. The horizontal strips of the tongue-and-groove connection between the strip-shaped composite panels produced reciprocating bite displacements, and ultimately improved the structure's energy dissipation capacity significantly.